Healthcare services in Palestine, overcoming the challenges and opportunities for improving quality of medical care: A narrative review - Al-Ramlawi, Doaa; Nurhaeni, Ismi Dwi Astuti; Nugroho, Rino Ardhian (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Palestinians face significant challenges in accessing quality healthcare due to various factors, including a shortage of medical professionals and facilities, inadequate infrastructure and equipment, political unrest, and violence. Despite efforts to reform the healthcare system, many Palestinians continue to struggle to obtain decent healthcare. This study conducted a narrative review using qualitative data collection methods to analyze the difficulties and possibilities for improving healthcare resources and services in Palestine. The research examined the current state of healthcare resources and services in Palestine and identified the primary challenges to expanding access to high-quality healthcare. These results align with the review’s goals by identifying areas that require enhancement to improve healthcare access and quality in Palestine. A narrative review of 18 articles revealed that Palestine's healthcare system requires significant improvements in many areas, such as infrastructure, financing, and governance, to address the existing issues. The formation of primary healthcare clinics increased financing for medical care, and the development of healthcare infrastructure and funding emerged as potential remedies for enhancing the healthcare system in Palestine. Substantial advancement in healthcare infrastructure, financing, and governance are necessary to ensure Palestinians have access to the healthcare services they need to thrive. Our study emphasizes the importance of addressing the challenges faced by the Palestinian healthcare system and highlights potential opportunities for improvement. By implementing the suggested remedies, policymakers and stakeholders can work towards enhancing the quality and accessibility of healthcare services in Palestine.